It Is Not Just Sharing Youth-Culture! It is A Spotify Music Branding through Instagram - Bunga Devina Nugroho; Yosefani Oktavia; Sukmo Banyu Jogo; Z. Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper aims to analyze the role of social media platform Instagram as a channel of marketing of musicians and their interaction with fans. Also, this paper analyzes youth-culture sharing behavior as a peer-to-peer digital marketing communication. Ethnographic was used as a research method with a long-term community observation, in-depth interviews, and online digital document analysis. Our paper focuses on studying the sharing youth-culture through Instagram, the practices of Instagram as a digital marketing communication channel of music product, and the personal musician branding. The results showed that the musicians as producers interact with their fans or consumers through social media Instagram. Collaboration through social media fosters sharing values and beliefs, exchanging daily experiences about music and cultural arts, young people build togetherness, from just interacting with doing business transactions on Instagram and Spotify. Musicians recognize the importance of digital channels as a marketing communication channel for music products so that Instagram has become a medium to build a reputation in the music field. Instagram provides opportunities for new talents from fans and further develops a network of indie musicians supported by Spotify. Instagram has become a home-branding for anyone who wants to be a musician and could gain a network of fans if it offers uniqueness and differentiation compared to competitors.